Improving Food Security through Entrepreneur Training for Fishermen’s Wives in Panjang Wetan Urban Village, Pekalongan City - Sobrotul Imtikhanah; Astarie; Wafie Latifa (Journal of Society, Community and Business Development, 2023)
North of Pekalongan is an area that has the greatest impact on rob. Tidal waves and Rob floods  are the main reason coastal communities are unable to carry out their daily activities, especially fishermen. Economically, dependence on fish catches is very high. Besides, fishermen's wives do not have the business skills to support their financial needs encourage universities to design service activities aimed at providing alternative solutions to economic problems for coastal communities. Through entrepreneurial work training activities for fishermen's wives, it is hoped that they can provide insight, knowledge and entrepreneurial skills as one solution so that fishermen's wives get additional household income.